Some Determinants of Disturbances of Social Functioning in Patients with Paranoid Schizophrenia with Related Viral Hepatitis - V. Rogov, Aleksey; K. Abdullaeva, Vasila; A. Matveyeva, Anastasiya; F. Sharipova, Parida; B. Irmukhamedov, Temur (International Journal of Psychosocial Rehabilitation, 2020)
Schizophrenia, like no other mental illness, is accompanied by a violation of social functioning - destabilization of personal relationships, separation from the family and society, and distortion of the usual forms of activity and communication. Social maladaptation as a result of the disease, which entails the disability of young and physically safe persons, leads to enormous economic costs for society. As a result of the study, it was found that with chronic HCV infection, a brain lesion occurs at the tissue level; the detected changes are a morphological substrate of the clinical manifestations of viral hepatitis. A significant factor for schizophrenia patients with chronic viral hepatitis is also the hepatotoxic effect of many psychotropic drugs. The purpose of the study was to determine the effect of impaired problem-solving behavior and a subjective assessment of the quality of life on the processes of social functioning in patients with paranoid schizophrenia with concomitant viral hepatitis.